Unintended Consequences and Hidden Obstacles in Medicine Access in Sub-Saharan Africa - Barton, Iain; Avanceña, Anton L. V.; Gounden, Nevashini; Anupindi, Ravi (Frontiers in Public Health, 2019)
Many life-saving drugs are still inaccessible and unaffordable in low- and middle-income countries, particularly in Sub-Saharan Africa. This contributes to poor health outcomes, wider health and socioeconomic inequities, and higher patient spending on healthcare. While resource limitations facing national regulatory authorities (NRAs) contribute to the problem, we believe that (1) fragmented and complex drug regulations, (2) suboptimal enforcement of existing regulations, and (3) poorly designed disincentives for non-compliance play a larger role. These “unintended consequences” that are a direct result of our current regulatory regimes limit competition, keep drug costs high, and lead to shortages and the proliferation of illegitimate and unregistered drugs. While NRAs can gain a lot from increased investment in their work, regulatory harmonization and innovation can arrest and reverse the regulatory failures we still see today and improve medicine access in Africa. Unfortunately, harmonization initiatives in Sub-Saharan Africa have made modest impact and have done so slowly. We encourage greater attention and investment in harmonization and other downstream functions of NRAs. We also urge increased participation of national governments–particularly executive agencies in health and the treasury—and patient advocacy groups in advancing harmonization across the subcontinent.